Experiences and Attitudes of Young People and Seniors in Relation to to People with Intellectual Disabilities - Kozáková, Zdeňka (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The contribution represents the selected summary of the results of research carried out through a questionnaire-based survey and a structured interview, the goal of which was to ascertain the experiences and attitudes of young people and seniorsin relation to mentally impaired individuals and define the spheres to which increased attention should be paid in the future. The examined group comprised 160 respondents. The contribution is introduced by information on the given issue and the definition of the basic terminology in relation to the examined sphere. Subsequently, it presents the methodological outcomes of the research and deals with specific results of the research and discussions. At the end, it summarizes the research conclusions in the context of various points of view of the current state of knowledge in theory and its application in practise.